Rancang Bangun Sistem Informasi Pengadaan Barang Menggunakan Client Server - Dwi Atmoko; Ervina Mahara; Nana Suarna (Jurnal Dimamu, 2022)
Based on the flow of direct procurement of goods including the direct procurement process, submission of bid documents and negotiations, the system currently used by Koperasi Asrama Yonif Para Raider 330 Nagreg is a manual system using records in paper or ledgers. From the current system, there are still weaknesses, namelydifficulties in processing, storing and searching data,delays in presenting information, inefficient time, and data inaccuracies,which can cause data loss and workload for employees. based procurement system client server which later could be implemented in the Yonif Para Raider 330 Nagreg Dormitory cooperative. The method used in this study is a qualitative descriptive method and the system development method uses the waterfall. The results of the research obtained were being able to find out the inventory procedures, being able to design information systems, being able to implement the existing information systems in the Nagreg Infantry Battalion 330 Raiders Dormitory.